IMPROVING STUDENTS READING COMPREHENSION THROUGH â€œSURVEY, QUESTION, READING, RECITE, REVIEW (SQ3R)â€ STRATEGY - Kasmawati, Kasmawati; Sakkir, Geminastiti (Universitas Negeri Makassar, 2020)
Abstract. The aims of this study was to find out whether or not of teaching of narrative text through SQ3R Strategy has improve students reading comprehension of X MIPA 1 class of SMA Negeri 4 Sidrap, South Sulawesi, Indonesia. This study used a pre-experimental method that consists pre-test and post-test. The total population is 90 students by taking one class as a sample using the quota sampling technique, namely class X MIPA 1 as a sample. The results of this study indicate the mean score of studentsâ€™ post-test (76.25) is greater than the pre-test (53.2). This shows a significant difference between students taught by using the SQ3R strategy in teaching reading comprehension of narrative texts. The results in pre-test and post-test that p-value was lower Î± (0,000 <0.05). This means that H1 is accepted and H0 is rejected. The concluded that teaching reading comprehension by implementation of SQ3R Strategy has influence to improve the students of X MIPA 1 class in SMA Negeri 4 Sidrap, South Sulawesi, Indonesia.